Vera. Set 1. [videorecording (DVD)] - Blethyn, Brenda, 1946-; Leon, David, 1980-; Mosaku, Wunmi; Cleeves, Ann (Distributed by Acorn Media, 2011)
Follows a solitary, obsessed, cantankerous investigator-- who happens to be pure genius at her job.